Verso-reverso em João Cabral do Melo Neto : Museu de tudo e depois - Carvalho, Karine Costa Branco de (2007)
Verso-reverso em João Cabral de Melo Neto Museu de tudo e depois discuss the question of depersonalization of the writing in the brazilian poet s work, focusing Museu de tudo, book the author defines as a new experience . Taking it as starting point for the retaken of I in his poetry, two moments are identified: before and after Museu de tudo. In the second moment, the ambiguous relation among the desire of impersonality and memorialistic substance, lyricism and antilyricism, reason and emotion becomes more evident.